Native Cell Environment Constrains Loop Structure in the Escherichia coli Cobalamin Transporter BtuB - Nyenhuis, David A. (Biophys J, 2020)
The extracellular loops of bacterial outer membrane (OM) transporters are thought to sample a range of conformations in the apo state but to undergo a gating motion and assume a more defined conformation upon the binding of substrate. Here, we use pulse electron paramagnetic resonance to examine the conformations of the extracellular loops of BtuB, the Escherichia coli TonB-dependent vitamin B(12) transporter, in whole cells. Unlike previous measurements carried out in vitro, the loops assume well-defined configurations in situ that closely match the in surfo crystal structures. Moreover, there is no evidence that the loops undergo significant gating motions upon the binding of substrate. The results demonstrate that the structure of BtuB is dependent upon an intact native OM environment, in which a critical component is likely to be the extracellular lipopolysaccharide. In general, this work indicates that measurements on OM proteins in reconstituted membrane systems may not reflect the native state of the protein in vivo.